Principle-Based Consumption Cash Waqf Management Formulation Mursalah Problems to Increase the Economic Resilience of the Community - Muhammad Alfalah Sebayang; Nispul Khoiri; Dhiauddin Tanjung (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to formulate a consumptive cash waqf management model based on the principle of maslahah mursalah as a strategic step in improving community economic resilience. Cash waqf, as an Islamic financial instrument, has significant potential in empowering the community's economy, especially if its management is dynamically adapted to the needs and conditions of the community. The principle of maslahah mursalah emphasizes efforts to achieve public welfare and prevent harm, thus becoming an important basis in designing an adaptive and effective waqf scheme. This research method uses a qualitative approach with literature analysis, interviews with waqf and Islamic economics experts, and case studies on waqf management that have been implemented. The results show that optimal management of consumptive cash waqf must be based on eliminating urgent needs such as financing for productive consumption, education, health, and preventative social assistance. In this formulation, cash waqf is not only philanthropic, but also aimed to create long-term economic impact by strengthening the purchasing power and financial resilience of poor and vulnerable families.